ANALISIS EFISIENSI EKONOMI DAN PRODUKSI KEPITING BAKAU (Scylla serrata) DALAM KARAMBA - Ta'aladin, Zamdial (Jurnal AGRISEP, 2004)
The objective  of this research  was to analyisis   of economic  efficiency,  production  of Muds Crab  that reared in  bambbo  cage and  to  determine  of  density  and  bamboo  cage  design  that  suffable  for  rearing  of  Mud Crab(Scylla   serrata).Research    was  used  the Factorial   Completely  Randomized   Design  with  the  dffferent treatement   consist  of density  and   bamboo cage construction.  Size of bamboo  cage are 2 x 2 x 0,5 m. The rearing periode  of Mud Crabs are 45 days wffh observation  and measurement  of weight and length growth in each  15 days.  For  determine  of  teratement  of density  and   bamboo  cage  construction  on the Mud  Crabs production  used  the statistical  test, while the economic  analysis was using BlC ratio  investement  criteria. The P1  ancJ P2  treatement   showed   the response of high   weight  growth  and signiflCBl1t with  Pl   The cell system bamboo  cage  showed    the respon~    of high  weight  growth  and Significant  from  the boxs  system  bamboo cage.    For  the length  growth,  P1 highly  and  significant   from  the others  treatement. The BlC  ratio  analysisi showed  that P3 treatement  both the cell and boxes system  bamboo cage  showed  the better result, while theP3  BIG ratio value of cell system  bamboo cage is highly in compare  with the boxes system bamboo cage.